Competitive intelligence - Conor Vibert (Thomson/South-Western, 2004)
Managers constantly face uncertainty as they attempt to make decisions in a complex and competitive environment. In Competitive Intelligence: A Framework for Web-Based Analysis and Decision Making, Conor Vibert gives the research professional a complete and reliable framework for collecting and analyzing information that will give managers confidence in any situation. Competitive Intelligence uniquely introduces the study of organizational theory and strategy into the competitive intelligence process to improve the effectiveness of competitive intelligence programs. Using Vibert's research missions, Internet search and analysis tools, and the analytical framework, researchers will have all they need to run an effective knowledge management program in an organization